2021
DOI: 10.48550/arxiv.2108.11094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing charged lepton flavor violation with axion-like particles at Belle II

Kingman Cheung,
Abner Soffer,
Zeren Simon Wang
et al.

Abstract: We study charged lepton flavor violation associated with a light leptophilic axion-like particle (ALP), X, at the B-factory experiment Belle II. We focus on production of the ALP in the tau decays τ → Xl with l = e, µ, followed by its decay via X → l − l + . The ALP can be either promptly decaying or long-lived. We perform Monte-Carlo simulations, recasting a prompt search at Belle for lepton-flavor-violating τ decays, and propose a displaced-vertex (DV) search. For both types of searches, we derive the Belle … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…There are two possible discriminators to tell the present MFV ALP from theirs. One is λ γ , because the flavor couplings in their setup are totally independent with each other, not constrained by MFV, so the parity violation is parametric, therefore no definite value of λ γ has been predicted in [80]. In contrast, the present MFV ALP is definitely right-handed specific for muon and electron, where the parity is broken only by the right-handed rotation in the framework of MFV, as emphasized in the previous section.…”
Section: Discrimination From Other Lfv Np Candidates In Light Of Bell...mentioning
confidence: 77%
See 2 more Smart Citations
“…There are two possible discriminators to tell the present MFV ALP from theirs. One is λ γ , because the flavor couplings in their setup are totally independent with each other, not constrained by MFV, so the parity violation is parametric, therefore no definite value of λ γ has been predicted in [80]. In contrast, the present MFV ALP is definitely right-handed specific for muon and electron, where the parity is broken only by the right-handed rotation in the framework of MFV, as emphasized in the previous section.…”
Section: Discrimination From Other Lfv Np Candidates In Light Of Bell...mentioning
confidence: 77%
“…• Second, in a recent paper [80], the authors focus on a light ALP having a high enough detection sensitivity at Belle II, through LFV and multi-lepton signals. Two parallel benchmark scenarios have been investigated in [80], where c ee and c eτ or c µµ and c µτ are turned on, respectively. There are two possible discriminators to tell the present MFV ALP from theirs.…”
Section: Discrimination From Other Lfv Np Candidates In Light Of Bell...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phenomenology studies on ALPs at e − e + colliders can be found in Refs. [44][45][46][47][48][49], and more studies can be found in the reviews [50][51][52][53][54][55] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Signatures of directly detectable or escaping long-lived particles at B factories have also been discussed in Refs. [30,[44][45][46][47][48][49][50][51][52][53][54][55] This paper is organized as follows: section 2 contains the theoretical framework of the RPV scenario. This includes the effective Lagrangian with the RPV terms and the calculation of the matrix elements, which we estimate using an effective BNV Lagrangian.…”
mentioning
confidence: 99%